Higher uptake of long‐acting reversible and permanent methods of contraception by Australian women living in rural and remote areas - Jayne C. Lucke; Danielle L. Herbert (Elsevier, 2014)
Abstract Objectives: To examine factors associated with the uptake of i) long‐acting reversible, ii) permanent and iii) traditional contraceptive methods among Australian women. Methods: Participants in the Australian Longitudinal Study on Women's Health born in 1973-78 reported on their contraceptive use at three surveys: 2003, 2006 and 2009. The participants were 5,849 women aged 25-30 in 2003 randomly sampled from Medicare. The main outcome measure was current contraceptive method at age 28-33 years categorised as long‐acting reversible methods (implant, IUD, injection), permanent (tubal ligation, vasectomy), and traditional methods (oral contraceptive pills, condoms, withdrawal, safe period). Results: Compared to women living in major cities, women in inner regional areas were more likely to use long‐acting (OR=1.26, 95%CI 1.03-1.55) or permanent methods (OR=1.43, 95%CI 1.17-1.76). Women living in outer regional/remote areas were more likely than women living in cities to use long‐acting (OR=1.65, 95%CI 1.31-2.08) or permanent methods (OR=1.69, 95%CI 1.43-2.14). Conclusions: Location of residence is an important factor in women's choices about long‐acting and permanent contraception in addition to the number and age of their children. Implications: Further research is needed to understand the role of geographical location in women's access to contraceptive options in Australia.